Types of questions teachers use and their importance in the reading classes of English - Nóbrega, Daniela Gomes de Araújo (Revista Leitura, 2019)
This article proposes to analyze the teacher's questions in English as a Foreign Language reading classes of the secondary school to verify the extent to which they use the questions from an adequate way to instigate students' critical reading. As part of my MA dissertation about Reading studies in English, I attempted to describe the teachers' profile in Florianópolis public schools, Santa Catarina, in the reading instruction by the questioning perspective to discuss pedagogical impllcations in the questions asked by those teachers. DOI: 10.28998/0103-6858.2007v1n39p159-172